2007
DOI: 10.1152/ajpcell.00450.2006
|View full text |Cite
|
Sign up to set email alerts
|

Large-conductance calcium-activated potassium channel activity is absent in human and mouse neutrophils and is not required for innate immunity

Abstract: Large-conductance Ca(2+)-activated K(+) (BK) channels are reported to be essential for NADPH oxidase-dependent microbial killing and innate immunity in leukocytes. Using human peripheral blood and mouse bone marrow neutrophils, pharmacological targeting, and BK channel gene-deficient (BK(-/-)) mice, we stimulated NADPH oxidase activity with 12-O-tetradecanoylphorbol-13-acetate (PMA) and performed patch-clamp recordings on isolated neutrophils. Although PMA stimulated NADPH oxidase activity as assessed by O(2)(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 49 publications
2
45
1
Order By: Relevance
“…It has recently been shown that BK channel activity is absent in neutrophils and is not required for antimicrobial defense (10,28). 1-EBIO is an activator of both calcium-activated potassium channel of intermediate conductance (IK) and SK channels (29); however, 1-EBIO does not activate IK channels in human neutrophils (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently been shown that BK channel activity is absent in neutrophils and is not required for antimicrobial defense (10,28). 1-EBIO is an activator of both calcium-activated potassium channel of intermediate conductance (IK) and SK channels (29); however, 1-EBIO does not activate IK channels in human neutrophils (11).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the calcium-activated potassium channel of small conductance (SK channel), which is the major calciumactivated potassium channel known to be present on neutrophils (8)(9)(10)(11), mediates NOX-independent neutrophil "apoptosis" (11). In this pathway, SK channels activate mitochondrial ROS production.…”
mentioning
confidence: 99%
“…It does not appear that the effects of NaHS-PC to prevent mucosal mitochondrial dysfunction can be attributed to a direct action on neutrophils or mast cells during I/R since recent reports indicate that BK Ca channel activity is absent in both human and mouse neutrophils whereas mast cell function is not inhibited by iberiotoxin, a highly selective BK Ca channel inhibitor (7,31). On the other hand, platelets express BK Ca channels, which, when activated, hyperpolarize platelet membranes, thereby limiting P-selectin expression and platelet adhesion to endothelial cells under static and flow conditions (22).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, potassium ions were proposed to provide the compensating charge and, by increasing the ionic strength within the phagosome, to activate cationic proteases required for bacterial killing (Reeves et al, 2002). However, the claim that Ca 2+ -activated K + channels (BK Ca ) are required for bacterial killing by neutrophils (Ahluwalia et al, 2004) was disproved because neutrophils lack BK Ca currents and kill microbes efficiently in the presence of BK Ca inhibitors or after genetic ablation of the BK Ca channel (Femling et al, 2006;Essin et al, 2007Essin et al, , 2009). Modeling indicates that other potassium channels and swellingactivated chloride channels (Ahluwalia, 2008) contribute no more than îș5% of the compensating charge, which is provided essentially by proton channels (Murphy and DeCoursey, 2006).…”
Section: And F)mentioning
confidence: 99%